Pengembangan E-Modul Ajar Informatika Untuk Meningkatkan Minat Belajar Dasar Program Keahlian SMK - Fajjriah, Nur; Atiqoh, Atiqoh; Hartono, Hartono (Universitas Negeri Malang, 2023)
Digital-era education requires innovative and adaptive approaches to ensure learning effectiveness. Grade 10 Pharmacy faces challenges in the problem of student interest in learning, especially in Informatics. The purpose of this research is to produce e-modules for teaching Informatics according to the criteria of good category e-modules in terms of media, material, and design and can increase student interest in learning. The development applies the ADDIE development model. This research has stages of needs analysis, designing an informatics e-module framework, developing teaching modules, applying modules in the learning process, and evaluation. The initial survey results showed that students' interest in learning was in the low category. The results of validation by material, media, and design experts were categorized as very good. To prove students' response to the e-book/informatics teaching module, it was tested through two stages, namely small group trials and large group trials. The results of the small group and large group tests reached the excellent/very feasible category. The average score obtained from the small group trial to the large group trial increased significantly. This shows that the informatics e-book/teaching module with a contextual approach developed is valid and feasible to use in the informatics learning process at school.AbstrakPendidikan era digital memerlukan pendekatan inovatif dan adaptif untuk memastikan efektivitas pembelajaran. Kelas X Farmasi menghadapi tantangan dalam permasalahan minat dalam belajar siswa, terutama dalam pelajaran Informatika. Keterlibatan teknologi informasi dalam pembelajaran menjadi kebutuhan utama dalam memotivasi dan merangsang minat pebelajar dalam belajar.Tujuan riset ini untuk menghasilkan e-modul ajar Informatika sesuai kriteria e-modul kategori baik secara media, materi, dan desain serta dapat memberikan peningkatan minat pebelajar dalam belajar. Pengembangan menerapkan model pengembangan ADDIE. Riset ini memiliki tahapan analisis kebutuhan, merancang kerangka e-modul informatika, mengembangkan modul ajar, menerapkan modul dalam proses belajar, dan evaluasi. Hasil survei awal menunjukkan minat dalam belajar pebelajar dalam kategori rendah. Hasil validasi oleh ahli materi, media, dan desain dikategorikan sangat baik. Untuk membuktikan respon pebelajar terhadap e-book/ modul ajar informatika dilakukan ujicoba melalui dua tahap yaitu uji coba pada kelompok kecil dan uji coba kelompok besar. Hasil uji kelompok kecil dan kelompok besar mencapai kategori sangat baik/sangat layak. Nilai rata-rata yang diperoleh dari uji coba kelompok kecil ke uji coba kelompok besar mengalami peningkatan cukup signifikan. Hal tersebut menunjukkan bahwa e-book/ modul ajar informatika dengan pendekatan kontekstual yang dikembangkan telah valid dan layak digunakan dalam proses pembelajaran informatika di sekolah